The Ethical Implication of Using Artificial Intelligence in Hiring and Promotion Decisions - Tabassam, Aliza; Yaqoob, Ghazala; Cuong, Vo Hung; Syed, Mashal; Shahzadi, Asma; Asghar, Fahad (2023)
A substantial increase in the use of Artificial Intelligence (AI) in the field of human resources, notably in the recruiting and promotion processes. This study investigates the ethical implications of using AI technology in these critical organizational choices. As AI-driven algorithms become more common in personnel management, the potential benefits of enhanced efficiency and impartiality must be balanced against the ethical considerations that arise. This study digs into the issues of algorithmic fairness, focusing on techniques for reducing prejudice in AI-driven recruiting and promotion systems. We investigate the significance of transparent AI procedures and techniques for holding AI systems responsible for their outputs and the ethical concerns of data usage, storage, and security in AI-powered human resource systems.